New techniques for jet calibration with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2023)
A determination of the jet energy scale is presented using proton-proton collision data with a centre-of-mass energy of √s = 13 TeV, corresponding to an integrated luminosity of 140 fb-1 collected using the ATLAS detector at the LHC. Jets are reconstructed using the ATLAS particle-flow method that combines charged-particle tracks and topo-clusters formed from energy deposits in the calorimeter cells. The anti-kt jet algorithm with radius parameter R=0.4 is used to define the jet. Novel jet energy scale calibration strategies developed for the LHC Run 2 are reported that lay the foundation for the jet calibration in Run 3. Jets are calibrated with a series of simulation-based corrections, including state-of-the-art techniques in jet calibration such as machine learning methods and novel in situ calibrations to achieve better performance than the baseline calibration derived using up to 81 fb-1 of Run 2 data. The performance of these new techniques is then examined in the in situ measurements by exploiting the transverse momentum balance between a jet and a reference object. The b-quark jet energy scale using particle flow jets is measured for the first time with around 1% precision using gamma+ jet events.
*ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 16.02.2024